UANG DALAM DUA DUNIA: PRAKTIK DAN PEMAKNAAN DALAM EKONOMI KONVENSIONAL DAN ISLAM - Intan Aulia Denada; Nuraini, Zakky Al Hussainy, Suci Hayati (Adisam Publisher, 2025)
Money is a fundamental element in the economic system that influences individual behavior, economic policy and social order. This article aims to compare the practice and meaning of money in conventional economics and Islamic economics. In conventional economics, money not only functions as a medium of exchange but also as a commodity that can be traded and speculated on, thus opening up space for usury practices and inequality in distribution. Meanwhile, Islamic economics views money as a medium of exchange that must be used productively and must not generate profits from the money itself. A descriptive qualitative approach is used through literature studies to examine the philosophical foundations and practical implications of the two systems. The results of the study show that Islamic economics emphasizes justice, balance and blessings in the use of money, in contrast to the materialistic approach in the conventional system